FRI0033 Mtor directed mesenchymal tissue response to inflammation in arthritis. (23rd January 2014) - Karonitsch, T.; Dalwigk, K.; Glehr, M.; Niederreiter, B.; Bilban, M.; Smolen, J.; Kiener, H.; Superti-Furga, G.
Abstract : Background: Accumulating evidence supports the concept that fibroblast-like synoviocytes (FLS) actively participate in the destructive, inflammatory process of rheumatoid synovitis. Thus, FLS frame a synovial microenvironment that augments and perpetuates synovial inflammation and mediates joint destruction. mTOR is best known for coupling energy and nutrient abundance to the execution of essential cellular processes, such as cell growth, cell survival or autophagy. More recent data, however, indicate that mTOR also directs the cellular response to inflammatory stimuli. Whether or not this also applies to FLS, particularily in the context of rheumatoid synovitis, remains elusive. Methods: To assess mTOR activity in rheumatoid arthritis (RA) FLS, immunhistochemistry (IHC) as well as immunoblotting (IB) was performed using phosphospecific antibodies to mTOR and downstream mTOR substrates. For functional in-vitro studies, the specific mTOR inhibitor Torin-1 was applied. The GeneChip PrimeView array was used for gene expression profiling. Assessment of regulated genes was determined via SAM analysis. The expression of selected candidates was validated by Q-PCR. To further evaluate the significance of mTOR activity for the mesencyhmal inflammatory tissue response, we used a previously described simplified 3-D model of the synovial tissue. IL-6 and IL-8 levels in the supernatants of 3-D cultures were measured by ELISA. Results: IHC revealed that the mTOR signalling cascade is activated in rheumatoid synovitis. In particular, mTOR, 4EB-BP and S6 were phosphorylated, especially in the hyperplastic synovial lining layer. In-vitro, stimulation of FLS with TNF resulted in the phosphorylation of mTOR, AKT, S6K1 and S6, indicating that TNF activates the mTOR cascade in these cells. To determine the effect of mTOR activation for the TNF driven mesenchymal inflammatory response, RA FLS (n=5) were exposed to TNF in the presence or the absence of Torin. TNF-stimulation resulted in the upregualted expression of 587 genes (fold induction>1, 5; FDR<0, 01). Surprisingly, 141 of those transcripts were further upregulated, when FLS were treated with TNF in the presence of Torin. Importantly, this group contained transcripts that are well known to be involved in RA pathogenesis, including IL-6, IL-8 and MMP1. Stimulation of the 3D synovial organ cultures with TNF resulted in hyperplasia of the lining layer at the surface of the spheres. Strikingly, treatment with Torin prevented TNF induced lining layer hyperplasia. In line with the gene expression studies, however, the combined treatment with TNF and Torin resulted in increased production of IL-6 as well as IL-8, when compared to cultures that were solely exposed to TNF. Conclusions: These studies provide insight into the regulatory circuits that determine the synovial mesenchymal tissue response to inflammation and suggest a multifaceted regulatory role for the mTOR signalling circuit in arthritis, especially in RA. Disclosure of Interest: None Declared